(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2020)
Globalisation brings significant challenges to economies worldwide. Smart specialisation is one of the tools that helps countries improve their innovation potential, thus improving their economic performance and competitiveness. Smart specialisation involves identifying a country’s competitive advantages in order to develop targeted strategies aimed at enhancing its competitiveness. The main objective of the paper is to identify innovation and smart specialisation challenges the European Union economies are facing. The paper aims to provide an overview of current innovation performance of the European Union Member States, as well as their smart specialisation strategies, focusing on their chosen thematic priority areas. In doing so, the contribution of the paper is twofold. First, it gives an overview of the main features of smart specialisation concept. Second, it provides an overview of innovation performance of the European Union Member States and their smart specialisation strategies.